RANCANG BANGUN JARINGAN AKSES MENGGUNAKAN METODEEOIP MELALUI JARINGAN SELULER - PRABAWA, SETYA AJI; Yulianton, Heribertus (Information Technology and Telematics, 2018)
Abstract - Data communication service providers need access networks to connect providers with customers so that data communication services can be used. Access network disruptions result in data communication services not being used by customers. The repair process that cannot be estimated has an impact on the customer's business processes being hampered. As a solution from the provider side, a portable access network is needed to backup customer connections temporarily during the access network repair process. This research designs and builds a portable access network solution by utilizing the cellular data connection and the MikroTik router. EoIP technology is combined with L2TP / IPSec to form a tunnel through the cellular internet network. The test results show, the latency of this portable access network is between 60-100 ms with low packet loss. Throughput is in the range of 2.7 Mbps on the HSPA cellular network. Transparent, able to allow various types of routing protocols. This portable access network is quite feasible to be used as a temporary solution when the main access network is interrupted. So that the service downtime does not too long.